Multiplatform next-generation sequencing identifies novel RNA molecules and transcript isoforms of the endogenous retrovirus isolated from cultured cells. Issue 5 (18th January 2018) - Moldován, Norbert; Szűcs, Attila; Tombácz, Dóra; Balázs, Zsolt; Csabai, Zsolt; Snyder, Michael; Boldogkői, Zsolt
Abstract: In this study, we applied short- and long-read RNA sequencing techniques, as well as PCR analysis to investigate the transcriptome of the porcine endogenous retrovirus (PERV) expressed from cultured porcine kidney cell line PK-15. This analysis has revealed six novel transcripts and eight transcript isoforms, including five length and three splice variants. We were able to establish whether a deletion in a transcript is the result of the splicing of mRNAs or of genomic deletion in one of the PERV clones. Additionally, we re-annotated the formerly identified RNA molecules. Our analysis revealed a higher complexity of PERV transcriptome than it was earlier believed. Abstract : The authors used short- and long-read RNA sequencing techniques along with PCR analysis to uncover a complex transcriptional landscape in the porcine endogenous retrovirus (PERV).